2001
DOI: 10.1002/jnr.1126
|View full text |Cite
|
Sign up to set email alerts
|

Multiple caspases are involved in ?-amyloid-induced neuronal apoptosis

Abstract: beta-amyloid peptide (Abeta) has been implicated in the pathogenesis of Alzheimer disease and has been reported to induce apoptotic death in cell culture. Cysteine proteases, a family of enzymes known as caspases, mediate cell death in many models of apoptosis. Multiple caspases have been implicated in Abeta toxicity; these reports are conflicting. We show that treatment of cerebellar granule cells (CGC) with Abeta25-35 causes apoptosis associated with increased activity of caspases-2, -3 and -6. Selective inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 33 publications
3
84
0
Order By: Relevance
“…[10][11][12][13][14] We therefore investigated the effect of 12-LOX downregulation on Ab-induced caspase activation. As shown in Figure 2, treatment of cortical cells with 25 mM Ab led to the activation of caspase-2, -3 and -8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] We therefore investigated the effect of 12-LOX downregulation on Ab-induced caspase activation. As shown in Figure 2, treatment of cortical cells with 25 mM Ab led to the activation of caspase-2, -3 and -8.…”
Section: Resultsmentioning
confidence: 99%
“…When combining these data to those previously obtained with the 12-LOX inhibitor, it thus appears that protection against neuronal death induced by Ab could be achieved upon blockade of 12-LOX through either inhibition of the enzyme or downregulation of its expression. Moreover, it is now well documented that caspases participate in Ab-induced apoptosis, [10][11][12][13] and that their activation correlates with apoptotic features in AD brains. 53,54 In particular, caspase-2, -3 and -8 have been reported to be activated in neurons following Ab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Aβ-induced apoptotic cell death in PC12 cells is associated with the decreased expression of the anti-apoptotic molecule Bcl-2 and the increased expression of the pro-apoptotic molecule Bax (Xiao et al, 2002;Yuyama et al, 2003). The activation of caspase-3 plays a role in Aβ-induced apoptosis (Allen et al, 2001) and an increase in activated caspase-3 has been reported in AD brains (Su et al, 2001). Therefore, the decrease in Bax or active caspase-3 expression and increase in Bcl-2 expression can provide a neuroprotective effect by inhibiting Aβ-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic cell death induced by Aβ is also associated with the neuritic degeneration and the onset of AD (Loo et al, 1993;Selkoe, 2000). In addition, the activation of caspase-3 plays a role in Aβ-induced apoptosis (Allen et al, 2001) and an increase in activated caspase-3 has been reported in AD brains (Su et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the experiments performed using caspase-3 inhibitors suggested that this caspase might also play a role in the generation of this fragment. A growing body of evidence suggests that caspases play a pivotal role in apoptosis induced by A␤ (Ivins et al, 1998(Ivins et al, , 1999Troy et al, 2000;Allen et al, 2001;Marques et al, 2003). Especially, caspase-3 is considered a key component of A␤-induced apoptosis in cultured neurons (Harada and Sugimoto, 1999;Marin et al, 2000;Allen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%